Bibliometric Analysis: Current Trends in the Relationship between Learning Motivation and Student Performance through the Influence of Learning Media, with a Focus on Augmented Reality in the Educational Context - Irfan Andi Gaffur; Nur Islami; Almasdi Syahra; Suarman Suarman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This bibliometric research analyzes 38 publications related to education over the past four years, focusing on the relationship between learning motivation and student performance. The analysis aims to determine the influence of learning media, especially Augmented Reality (AR), on student motivation and performance. A qualitative descriptive method is employed to detail data from international journal articles indexed in Scopus (Q1-Q2). The study also applies a systematic analysis using the PRISMA method to identify relevant articles. The analysis results indicate that keywords such as